Halal Certification Role as Mediation in Efforts to Increase Halal Awareness, Customer Value, and Purchasing Decisions on DKI Jakarta’s Halal Culinary Consumers - Victor Pascalis Gazali; Fahrul Riza (Eduvest - Journal of Universal Studies, 2024)
The purpose of this study is to determine the role of Halal Certification in improving the relationship between Halal Awareness to Customer Value which results in improved Pur-chasing Decisions. The research methodology was carried out using quantitative purposive sampling methods with a total of 213 Muslim respondents who ate and drank in restau-rants or restaurants in office areas in South Jakarta in 2023 by directly distributing ques-tionnaires. The data analysis technique uses SEM-AMOS version 24. The results of this study prove that the indirect effect of Halal Certification has a mediating role in increasing the influence of Halal Awareness on Customer Value, whereas the direct effect of the in-fluence of Halal Awareness on Customer Value has a negative estimated value and a sig-nificant p-value. The higher one's Halal Awareness will make consumers more careful, and critical, and choose a product. This research also proves that Halal Certification has an im-portant role in customer value so that products are guaranteed Halalan Tayyiban. This re-search implies that it can be a reference for academic research and seminar materials. Business actors can also make strategic planning in business development in product mar-keting and consumers can participate by not bringing non-halal food and beverages into restaurants or restaurants that have been guaranteed to be Halal. Further research can be developed in the field of strategic management, making the variables Theory of Planned Behavior, Theory of Reasoned Action, and 4P & 4C Marketing Mix as mediating variables.